2018
DOI: 10.1080/10942912.2018.1489836
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis of chicken, duck, and quail egg yolks

Abstract: A comparative analysis of egg yolk proteome of three major poultry species, namely, chicken, duck, and quail, was carried out with two-dimensional (2D) gel electrophoresis patterns and matrix-assisted laser desorption/ionization time-of-flight tandem mass spectrometry. Proteins identified from these three poultry species shared high degrees of sequence and structure homology, which might be related to the bird's adaptability under different environmental stresses. Few specific proteins were found in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 36 publications
(40 reference statements)
5
25
0
Order By: Relevance
“…Ovomucin (mucin-5B and mucin-6) has been identified as absent from egg yolk in all previous proteome studies [ 3 , 5 , 19 , 20 ], suggesting that ovomucin is exclusively distributed in the outer layer of the CEVM. The structure-specific distribution of ovomucin is closely related to the different origins of the inner and outer layers of the CEVM.…”
Section: Resultsmentioning
confidence: 88%
“…Ovomucin (mucin-5B and mucin-6) has been identified as absent from egg yolk in all previous proteome studies [ 3 , 5 , 19 , 20 ], suggesting that ovomucin is exclusively distributed in the outer layer of the CEVM. The structure-specific distribution of ovomucin is closely related to the different origins of the inner and outer layers of the CEVM.…”
Section: Resultsmentioning
confidence: 88%
“…Vitellogenin, as a phospholipoglycoprotein, extensively exists in non‐mammals, not only facilitates the growth and differentiation of animal oocytes but also provides nutrients for the developing embryos (Liu, Qiu, Gao, & Ma, ). Among the 12 spots identified as VTG, four spots (14, 15, 16, and 22) increased significantly in abundance after day 14 of incubation (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides these chemical compounds, some variability in bioactive molecules were also reported. Indeed, the comparative analysis of egg-white and egg-yolk proteomes revealed some proteins that are specifically associated with one or the other species [194,195,196,197] and others (ovotransferrin, lysozyme, gallin), displaying difference in abundance [196]. Overall, these characteristics may affect the overall bioactive potential of egg-white extract (antibacterial and/or antioxidant activity) depending on its bird origin, and it was shown that egg white from chicken egg retains the highest antibacterial potential compared to egg white from turkey, duck, and goose, at least, against some bacterial strains (Bacillus subtilis, Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli) [91].…”
Section: Factors Affecting Egg Qualitymentioning
confidence: 99%